The Digital Consumer Economy: Purchasing Behavior of Youth in E-Commerce Markets - Shrestha, Hira Lal; Dhital, Krishna Prasad; Shrestha, Anusha; Tramu, Gita; Sejuwal, Narendra (NPRC Journal of Multidisciplinary Research, 2025)
Background: The e-consumer economy is expanding by leaps and bounds, with youths being the prime drivers of growth in e-commerce. Businesses and platforms looking to survive in competitive online economies, such as Nepal, must have an understanding of youth buying habits and behavior.Objective: The aim of this research was to explore Nepalese youth's platform preference and relative importance assigned to various website features with regards to buying behavior through e-commerce, as well as a gender comparison and age group.Methods: Between January and May 2025, there was a cross-sectional, quantitative study conducted. Data were collected from an online survey of a sample of 202 Nepalese online users. The questionnaire collected demographic data, usage of the platform, and perceptions regarding e-commerce features on a 5-point Likert scale. Data analysis employed descriptive statistics, independent samples t-tests, Pearson correlation, and bootstrapping for validation.Findings: The sample was evenly divided by gender (51% female, 49% male) and consisted mostly of well-educated young adults aged 21-25 years (60.9%) with easy internet access (74.8%). Daraz was the overwhelmingly leading platform, as 89.6% of respondents used it. Respondents exhibited high consistency and agreement on the crucial importance of all e-commerce features assessed, and the most highly prioritized items were ease of price comparison (Mean=1.85) and ease of website usability (Mean=1.89). There was significant gender disparity, and the females were in greater agreement on the importance of these features compared to the males (p=.032). There was a small positive correlation between age and feature importance (r=.167, p=.017) and this was corroborated by bootstrapping (95% CI: .055, .283).Conclusion: The research concludes that Nepalese youth are homogeneous in terms of platform selection but have strong and particular expectations for their e-commerce experience, valuing convenience, cost-effectiveness, and ease of use. Gender and, to a lesser degree, age are important factors impacting such expectations.Implication: The e-commerce organizations, particularly the market leaders like Daraz, must maintain a frictionless shopping experience, price transparency, and robust logistics to support the high aspirations of young consumers. Marketing and platform development initiatives must be customized to support the slightly higher expectations of women consumers.